Extent of Adoption of System of Rice Intensification (SRI) Practice in India - B. , Johnson,; Vijayaragavan, K.; Singh, Premlata (Indian Journal of Extension Education, 2012)
The present paper explores the extent of adoption of System of Rice Intensification (SRI) practice in India. The extent of adoption is measured as the percentage of actual practice to recommended SRI practice. The present research was undertaken in Andhra Pradesh and Tamil Nadu states where SRI was introduced first in our country. A total of 100 respondents (50 from each state) were selected through proportionate random sampling technique. An ex-post-facto research design was used. Data collection was done through interview method. The overall extent of area of adoption of recommended SRI practice by the respondents was 70.6 per cent.Around one-third of respondents in Tamil Nadu and one-fourth of the respondents in Andhra Pradesh state adopted recommended SRI practice in 81 to 100 per cent area to total area under cultivation. Nearly one-third of the respondents in both Tamil Nadu and Andhra Pradesh adopted 71-80 per cent of recommended SRI practice. Only 15 per cent of respondents adopted 91-100 per cent of recommended SRI practice. Practice wise analysis revealed that nursery area and seed rate were found to be over adopted. Majority of respondents transplanted 8-15 days old seedlings and placed the root at 1-2cm depths. Almost all respondents adopted wider spacing in square patterns. Nearly three-fourth of the respondents transplanted one seedling per hill. Little above half of the respondents adopted levelling the field, marking on the field at 25cm interval with a marker and cono-weeding. Half of the respondents adopted application of more organic manure and less of fertilizer and agro-chemicals. Only 40 per cent of the respondents adopted alternate wetting and drying practice for water management. The most important factors which influenced respondents for adoption of SRI practice were a lower seed rate, high grain and straw yield, less cost of cultivation and to obtain subsidies. Other factors were motivation by extension official and friends and neighbours and water requirement are less.
Keywords: SRI; Adoption; Extent of adoption; Extent of area of adoption; Practice wise extent of adoption